Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.33073/pjm-2014-022
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Sulfonamide Resistance Genes via in situ PCR-FISH

Abstract: Due to the rising use of antibiotics and as a consequence of their concentration in the environment an increasing number of antibiotic resistant bacteria is observed. The phenomenon has a hazardous impact on human and animal life. Sulfamethoxazole is one of the sulfonamides commonly detected in surface waters and soil. The aim of the study was to detect sulfamethoxazole resistance genes in activated sludge biocenosis by use of in situ PCR and/or hybridization. So far no FISH probes for the detection of SMX res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…The activated sludge has been already reported as a niche rich in sul 1–3 and integrons (e.g., Tennstedt et al 2003 ). Those resistance determinants were also detected in the activated sludge samples obtained from the same WWTP and used in the previous study (Luczkiewicz et al 2013 ; Gnida et al 2014 ). In wastewater processes, class 1 integrons are suggested to serve as an important reservoir of resistance genes, mainly those encoding resistance to disinfectants ( qac EΔ1) and sulfonamides ( sul 1) (Enne et al 2001 ; Huovinen et al 1995 ; Huovinen 2001 ; Sköld 2001 ).…”
Section: Resultssupporting
confidence: 54%
“…The activated sludge has been already reported as a niche rich in sul 1–3 and integrons (e.g., Tennstedt et al 2003 ). Those resistance determinants were also detected in the activated sludge samples obtained from the same WWTP and used in the previous study (Luczkiewicz et al 2013 ; Gnida et al 2014 ). In wastewater processes, class 1 integrons are suggested to serve as an important reservoir of resistance genes, mainly those encoding resistance to disinfectants ( qac EΔ1) and sulfonamides ( sul 1) (Enne et al 2001 ; Huovinen et al 1995 ; Huovinen 2001 ; Sköld 2001 ).…”
Section: Resultssupporting
confidence: 54%
“…Numerous studies have shown that ARB and ARGs related to quinolones (Lindberg et al, 2006; Kaplan et al, 2013), tetracyclines (Huang et al, 2014; Li et al, 2013), and sulfonamides (Collado et al, 2013; Gnida et al, 2014) could be found within various types of biosolids (nutrient rich organic matter that is a by‐product of wastewater and sewage sludge treatment). Additionally, several antibiotic resistance plasmids including MDR pAS1 and RP4 carrying resistance to tetracycline, chloramphenicol, ampicillin, kanamycin, and many other antibiotics have been found in the diverse bacterial communities of activated sludge (Dröge et al, 2000; Parsley et al, 2010; Soda et al, 2008; Zhang et al, 2011).…”
Section: Challenges In Measuring Background Levelsmentioning
confidence: 99%